Case Report: The Effects of Massage Therapy on a Woman with Thoracic Outlet Syndrome - Wakefield, Mary Lillias (Int J Ther Massage Bodywork, 2014)
INTRODUCTION: Thoracic outlet syndrome (TOS) refers to a group of conditions resulting from compression of the neurovascular structures of the thoracic outlet. The parameters for physical therapy include myofascial release (MFR), neuromuscular therapy (NMT), muscle strengthening, and stretching. This case study examined the effects of neuromuscular therapy, massage, and other manual therapies on a 56-year-old female presenting with bilateral numbness over the forearms and hands on waking. Numbness occurred most days, progressing to “dead rubbery” forearms and hands once or twice a month. METHODS: The treatment plan was implemented over eight weeks and consisted of six, 50-minute bodywork sessions. Several nonbodywork strategies were also employed to address potential contributing factors to the TOS symptomology experienced by the client. Objective measurements included posture analysis (PA), range of movement (ROM), and Roos and Adson’s tests. The Measure Your Own Medical Outcome Profile (MYMOP2), a client-generated measure of clinical outcome, was used to measure clinical change. RESULTS: MYMOP2 overall profile score results demonstrated an improvement of 2.25 from pretreatment to post-treatment measurement. Clinically meaningful change was measured by the individual and was indicative of substantial symptom improvement where a score change of over one was considered as meaningful. CONCLUSIONS: A course of massage was effective for numbness symptoms in an individual with TOS, and results lasted over a year without additional treatments. Further research is needed to fully understand the effects of massage for TOS symptoms.